Field Corn Production Guide - David Wright; Ian Small; Cheryl Mackowiak; Zane Grabau; Pratap Devkota; Silvana Paula-Moraes (EDIS)
This publication discusses several aspects of field corn production in Florida, such as economics, land preparation, hybrid selection, fertilization, irrigation, and disease management. Written by David Wright, Ian Small, Cheryl Mackowiak, Zane Grabau, Pratap Devkota, and Silvana Paula-Moraes, and published by the UF/IFAS Agronomy Department, revised August 2022.